2015
DOI: 10.5897/ajar2013.8072
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal activity of polyphenols-rich plant extracts against Phytophthora cinnamomi Rands

Abstract: Antifungal activity of water, ethanol, lanolin and cocoa butter plant extracts derived from seven Mexican Chihuahuan desert inhabiting plant species (Larrea tridentata, Flourensia cernua, Agave lechuguilla, Opuntia ficus-indica, Lippia graveolens, Carya illinoensis and Yucca filifera)were evaluated against Phytophthora cinnamomi. All plant extracts were active against Phytophthora cinnamomi. Two (L. tridentata and F. cernua) out of seven plant species tested had the optimal antifungal activity against this fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Additionally, these emulsions inhibited the mycelium growth of R. solani at concentrations of 1.70 × 10 4 and 6.72 × 10 3 mg/L, respectively. Similarly, Francisco et al [119] confirmed the antifungal activity of lanolin extract of this species against P. cinnamomi at IC 50 of 23.07 mg/mL. In contrast, lanolin extract exhibited an antifungal concentration lower than ethanolic extract but similarly to aqueous extract (28.87 mg/mL), which suggested that lanolin emulsions can also be efficient solvents to recover bioactive compounds.…”
Section: Antifungal Activitymentioning
confidence: 81%
“…Additionally, these emulsions inhibited the mycelium growth of R. solani at concentrations of 1.70 × 10 4 and 6.72 × 10 3 mg/L, respectively. Similarly, Francisco et al [119] confirmed the antifungal activity of lanolin extract of this species against P. cinnamomi at IC 50 of 23.07 mg/mL. In contrast, lanolin extract exhibited an antifungal concentration lower than ethanolic extract but similarly to aqueous extract (28.87 mg/mL), which suggested that lanolin emulsions can also be efficient solvents to recover bioactive compounds.…”
Section: Antifungal Activitymentioning
confidence: 81%
“…(Munguía et al, 2014). Francisco et al (2015) assessed the in vitro antifungal activity of L. tridentata water, ethanol, lanolin, and cocoa butter extracts against P. cinnamomi, the ethanol extract completely inhibited mycelium, while the lanolin extract showed very low inhibition. L. tridentata ethanol and dichloromethane extracts reduced fungal growth by 75-100% against A. tenuissima, A. niger, Penicillium polonicum, and Rhizopus oryzae.…”
Section: Introductionmentioning
confidence: 99%